How Allogeneic Hematopoietic Stem Cell Transplantation has Evolved Over Time: 30-Years’ Experience at a Single Institution - Abecasis, Manuel (2020)
Introduction: Allogeneic stem cell transplantation is an established procedure for a variety of diseases of the hematopoietic system. Our transplant program started in 1987 and since then advances have been made in the care of patients undergoing transplantation. We conducted a study to evaluate whether the changes implemented over time have improved the outcomes of transplantation.Material and Methods: We analyzed changes in patients, cell source, transplantation and outcome among 682 consecutive patients receiving their first transplant between 1987 and 2016. We compared overall survival, progression-free survival, the incidence of nonrelapse mortality and relapse in 10-year cohorts over the three decades of the study.Results: The median age of transplanted patients, the use of peripheral blood and unrelated donors all increased very significantly. There was an increase in the number of high-risk patients when comparing the first decade with the two subsequent ones. The 3-year non-relapse mortality decreased significantly from 29% to 20% (p = 0.045), while the overall survival, progression free survival and cumulative incidence of relapse remained stable.Discussion: Allogeneic hematopoietic stem cell transplantation has evolved considerably since its introduction in clinical practice. In the present study, we evaluated how these changes affected our practice along 30 years of activity and compared the results with those published in the literature.Conclusion: Despite increasing age, higher risk patients and the increasing use of unrelated donors our results show a continuous significantly reduced non-relapse mortality, with stable overall survival, progression free survival and relapse rate.